2023
DOI: 10.1073/pnas.2211996120
|View full text |Cite
|
Sign up to set email alerts
|

Circadian regulation of hippocampal function is disrupted with corticosteroid treatment

Abstract: Disrupted circadian activity is associated with many neuropsychiatric disorders. A major coordinator of circadian biological systems is adrenal glucocorticoid secretion which exhibits a pronounced preawakening peak that regulates metabolic, immune, and cardiovascular processes, as well as mood and cognitive function. Loss of this circadian rhythm during corticosteroid therapy is often associated with memory impairment. Surprisingly, the mechanisms that underlie this deficit are not understood. In this study, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…The two receptor types bind the same downstream response elements, but studies in rats detect a high occupancy of the mineralocorticoid receptor even at circadian trough levels due to a strong binding affinity of corticosterone [47, 50, 51]. However, even with a high basic occupancy, the amount of mineralocorticoid receptor bound to the glucocorticoid response element in the Per1 promoter still exhibits a circadian rhythm [47] as does the binding of the glucocorticoid receptor [30], indicating that under physiological conditions, both receptor types are susceptible to corticosterone activation during the daily hormone increase, thus highlighting the biological importance of the endogenous ligand. The receptor binding patterns of corticosterone and dexamethasone also vary between brain regions, so while corticosterone is bound in higher concentrations in the hippocampus as compared to the anterior pituitary, the opposite pattern was the case for dexamethasone [52, 53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two receptor types bind the same downstream response elements, but studies in rats detect a high occupancy of the mineralocorticoid receptor even at circadian trough levels due to a strong binding affinity of corticosterone [47, 50, 51]. However, even with a high basic occupancy, the amount of mineralocorticoid receptor bound to the glucocorticoid response element in the Per1 promoter still exhibits a circadian rhythm [47] as does the binding of the glucocorticoid receptor [30], indicating that under physiological conditions, both receptor types are susceptible to corticosterone activation during the daily hormone increase, thus highlighting the biological importance of the endogenous ligand. The receptor binding patterns of corticosterone and dexamethasone also vary between brain regions, so while corticosterone is bound in higher concentrations in the hippocampus as compared to the anterior pituitary, the opposite pattern was the case for dexamethasone [52, 53].…”
Section: Discussionmentioning
confidence: 99%
“…The glucocorticoid receptor is widely distributed in the brain with a high concentration in the hippocampus [2629]. At the molecular level, a functional glucocorticoid receptor response element has been identified in the promoter of the clock genes Per1 [30] and Per2 [31]. A set of studies combining adrenalectomy and injection of corticosterone in rats have reported glucocorticoid-dependent effects on the expression of clock genes in the prefrontal cortex [32], the bed nucleus of the stria terminalis, and the amygdala [7, 33], whereas timely controlled rhythmic infusion of corticosterone at physiological levels has been shown to drive clock gene rhythms in the cerebellum [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evidence for GR’s involvement in the transcriptional regulation of Npy in the arcuate nucleus does not preclude an additional involvement of the MR since both GR and MR are highly expressed in the arcuate nucleus 33 35 . However, because MR has 10 fold higher affinity for CORT than GR it is near maximally bound even at low CORT levels circulating during the circadian nadir, while in contrast the lower affinity GR becomes activated with the higher CORT levels of an ultradian pulse peak within the circadian active phase 36 39 and therefore provides a more responsive and dynamic sensor of fluctuating CORT levels over the day. Accordingly, GR is generally thought to be more likely to initiate transcriptional responses to higher CORT levels.…”
Section: Discussionmentioning
confidence: 99%
“…In order to stay synchronized with the external environment, circadian clocks rely on external signals called zeitgebers or timing cues to undergo phase resetting [ 32 , 34 ]. The retinohypothalamic tract primarily entrains the SCN through exposure to external light, whereas neurohormonal factors exert an influence on peripheral clocks and mealtimes [ 35 , 36 ], and peripheral tissues can be moderately affected by nonphotic signals, such as food intake and glucocorticoids [ 37 , 38 ]. The nervous and endocrine systems both regulate the peripheral clocks in vivo.…”
Section: Regulation and Control Of The Circadian Body Clocksmentioning
confidence: 99%